KARAKTERISTIK PASIEN DAN POLA PENYAKIT RAWAT JALAN DI RUMAH SAKIT AL-ISLAM BANDUNG - Ceria Febiana (LPPM Universitas Awal Bros, 2025)
Outpatient services represent the primary point of contact between patients and hospitals and serve as an important indicator of healthcare service quality. High outpatient visit volumes require hospitals to understand patient characteristics and disease patterns in order to align services with population needs. This study aimed to analyze patient characteristics and outpatient disease patterns at Al-Islam Hospital Bandung in 2024. A descriptive quantitative study with a retrospective approach was conducted using secondary data from the hospital’s Electronic Medical Records. A total of 400 outpatient records were randomly selected from a population of 33,550 visits using the Slovin formula with a 5% margin of error. The variables analyzed included sex, age group, place of residence, and primary diagnosis. The results showed that outpatient visits were predominantly made by female patients (57%) and individuals in the adult age group of 19–59 years (53.8%), with most patients residing in Bandung City (68%). The five most common primary diagnoses were Follow-Up Examination After Unspecified Treatment for Other Conditions (Z09.9), Counselling, Unspecified (Z71.9), Follow-Up Examination After Other Treatment for Other Conditions (Z09.8), Pulpitis (K04.0), and Necrosis of Pulp (K04.1). Cramer’s V analysis indicated no significant association between disease patterns and sex, while a significant association was observed between disease patterns and age categories. In conclusion, outpatient services at Al-Islam Hospital Bandung are predominantly utilized by adult and elderly patients with conditions requiring ongoing follow-up and long-term monitoring, reflecting a shift from acute care toward chronic disease management.